Keefektifan Penerapan Media Pop Up dalam Pembelajaran Menulis Cerpen - Suarni Syam; Nensilianti Nensilianti (Seminar Nasional LP2M UNM, 2019)
This study aims to determine the learning outcomes of writing short stories before and after pop-up media is applied and to determine the effectiveness of the results of using pop-up media . This type of research is a type of experimental research with one group pretest-posttest (the group pretest-posttest). this study it was found that the value of students after using pop-up media increased significantly compared to students' scores before using pop-up media in writing short stories. obtained by students in writing short stories. can be stated that the ability to write short stories after using pop-up media is well developed. Problems that occur before using media pop ups can be solved by using media pop ups.. Conclusion the application of pop-up media in learning to write short stories is effectively used. Thus visual media, especially pop-up media can be a solution and an alternative to designing creative writing learning, especially writing short stories.